Changes in Endoglucanase Patterns during Growth of Thermomonospora curvata on Cellulose - Lupo, Davis (1988)
The endoglucanases of the thermophilic actinomycete Thermomonospora curvata were characterized. Early-exponential-phase culture fluid contained at least three endoglucanases, with molecular weights of 23,000, 46,000, and 146,000 and K(m) values of 1.54, 3.60, and 1.32% carboxymethyl cellulose, respectively. The stationary-phase pattern was altered to include three enzymes with molecular weights of 52,000, 114,000, and 106,000, with respective K(m) values of 1.77, 8.30, and 1.91%.